PENGARUH JAMINAN, TENOR, DAN PELAYANAN TERHADAP KEPUTUSAN PEMBIAYAAN MURABAHAH PADA BANK 9 JAMBI SYARIAH CABANG SIMPANG 4 SIPIN - Sissah; Refky Fielnanda; Tania (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The purpose of this study was to determine and analyze the effect of collateral, tenor and service on customer decisions to choose Murabahah financing at Bank 9 Jambi Syariah. This research is a descriptive quantitative research. The data used is primary data obtained from distributing questionnaires to customers of Bank 9 Jambi Syariah who do the financing. The research sample was obtained from the purposive sampling technique with the Slovin formula, 94 respondents were obtained. Data analysis technique using Multiple Regression Analysis. The results showed that: 1) Collateral has an influence on the customer's decision to choose Murabahah financing at Bank 9 Jambi Syariah with a significance value of 0.000 <0.05; 2) The tenor has an influence on the customer's decision to choose Murabahah financing at Bank 9 Jambi Syariah with a significance value of 0.015 <0.05; 3) Service has an influence on the customer's decision to choose Murabahah financing at Bank 9 Jambi Syariah with a significance value of 0.000 <0.05; and 4) Collateral, tenor, and service together influence the customer's decision to choose Murabahah financing at Bank 9 Jambi Syariah with an influence of 68.5%.